Board Composition: Balancing Family Influence in S&P 500 Firms - Anderson, Ronald C.; Reeb, David M. (Administrative Science Quarterly, 2004)
We examine the mechanisms used to limit expropriation of firm wealth by large shareholders among S&P 500 firms with founding-family ownership. Consistent with agency theory, we find that the most valuable public firms are those in which independent directors balance family board representation. In contrast, in firms with continued founding-family ownership and relatively few independent directors, firm performance is significantly worse than in non-family firms. We also find that a moderate family board presence provides substantial benefits to the firm. Additional tests suggest that families often seek to minimize the presence of independent directors, while outside shareholders seek independent director representation. These findings highlight the importance of independent directors in mitigating conflicts between shareholder groups and imply that the interests of minority investors are best protected when, through independent directors, they have power relative to family shareholders. We argue that expanding the discussion beyond manager-shareholder conflicts to include conflicts between shareholder groups provides a richer setting in which to explore corporate governance and the balance of power in U.S. firms.